Upaya Peningkatan Literasi Dengan Pengadaan Pojok Baca Dan Bimbingan Belajar Pada Siswa Di SDN Karang Asih 02 - Muhammad Rayhan Diza (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
This research addresses the issue of low literacy among students at SDN Karang Asih 02 by implementing the "Pojok Baca dan Bimbingan Belajar". Through methods of observation, analysis, and coordination with the school, along with book donation activities, this program successfully increased students' interest in reading and their literacy skills. Evaluation results indicate that students became more enthusiastic about reading, reducing negative stigmas associated with reading activities, and achieving a significant improvement in reading abilities. The findings demonstrate that this strategy is effective in enhancing student literacy and contributes positively to building a stronger reading culture within the school.